Artificial Intelligence in Higher Education in Libya: Opportunities and Challenges (Sebha University Conference Proceedings, 2025)
The educational system is one of the ancient systems characterized by conservatism, which requires protection from repeated and emergency changes, while at the same time the desire to prepare and equip students for the job market and the needs of society. For the application of artificial intelligence in the educational process, there have been arguments supporting and others rejecting it. There are concerns that if it is activated, education may deviate from its main goal, which is to provide students with reliable knowledge according to specific standards, and if it is not activated, the educational system will lag behind the rapid development and progress in artificial intelligence applications related to artificial intelligence. From this point of view, this research aims to study the possibility of using and employing artificial intelligence in higher education through a SWOT (Strengths, Weaknesses, Opportunities, Threats) analysis. The analysis showed that the opportunities outweigh the threats in applying artificial intelligence, and it highlighted the most prominent constraints imposed on it and the risks that may occur in the future and the potential problems if the threats are not overcome and the weaknesses are reduced. The study concluded that applications of artificial intelligence are good and very useful for both faculty and students, and they improve their efficiency and performance, but this is done with care in the presence of controls and laws, with an emphasis on originality in the educational process, credibility, and respect for the principle of equality.